Dynamics of Organizational Education of West Java Ulama Association - Syahwalan, Syahwalan; Ansori, M. Afif; Andari, An An (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this research is to describe the educational dynamics of the West Java Ulama Association organization. The research method used is qualitative research. Data obtained came from literature searches or literature studies on educational dynamics in West Java ulama union organizations. The data used is primary data. Sources of data were obtained from books and journals of the West Java Ulama Association. Data analysis using content analysis. The study results stated that the Ulama Association was a manifestation of the renewal movement in the Majalengka area, West Java. Ulama Association is a renewal movement founded by KH. Abdul Halim in 1887 in Cibelerang, Majalengka, West Java. KH. Abdul Halim founded Hayatul Qulub, which is engaged in education & in the economic field. Finally, after four years of activity, in 1915, the Hayatul Qulub organization was closed by the government due to fights with traders from China in 1916 KH. Abdul Halim founded Majlisul 'Ilmi, which is well connected with Jam'iat Khair & Al-Irsyad in Jakarta. Then, in 1917, assisted by H.O.S. Cokroaminoto, it became the Ulama Association. The Ulama Association Education System has two stages. First, the Alaqah system or traditional education system, the halaqah system is also called the Weton system, namely where the students take lessons by sitting around kiai in the room, and kiai explains the material in lectures. Second, the modern education system is an education model that uses classes using chairs and tables that are guided and/or organized in the form of class levels over a period of time. The influence of the establishment of the Ulama Association on the Education System increased knowledge such as religious, social, arithmetic, and linguistics, as well as skills teaching. Based on this description, it can be concluded that in development, the organization of the ulama union experienced various changes from time to time.